The effect of market conditions on the housing outcomes of subsidized households: the case of the US voucher programme. Issue 9 (21st October 2019) - Colburn, Gregg
Abstract: Since being created in the 1970s, housing vouchers have become the primary mode of federal housing support for low-income households in the US. The voucher programme was designed to provide recipients with the mobility needed to secure higher quality housing in neighbourhoods of their choice. Decades of analysis suggest that the programme has failed to produce the favourable outcomes envisioned by policymakers. To add to our understanding of the outcomes of this important federal programme, this paper seeks to underscore the importance of context-dependent policy analysis. In particular, this study analyses the impact of housing market conditions on the outcomes achieved by voucher recipients. Using neighbourhood and housing outcome data from the American Housing Survey, and median rent and rental market vacancy data, this paper demonstrates the important role that market conditions play in programme outcomes. The results from this study suggest that voucher recipients are successful at improving housing unit quality outcomes regardless of market conditions, but the ability to move to a better neighbourhood is a function of vacancy rates.